PHILOSOPHY ANDHUMANISM DURING THE REIGN OF AMIR TEMUR - Narzullaeva Farzona Farhodovna (International Journal of Innovations in Engineering Research and Technology, 2021)
The spiritual heritage of the Temurids is one of the brightest pages of world history. The brilliant take-off of science, architecture, urban planning, visual and applied arts, literature, poetry, music is a unique phenomenon of a global scale. The article notes that Sahibkiran Amir Temur left a huge mark in world history not only as a great statesman and commander, but also as a patron of art and science.